Defect remedy in hostel building in Universiti Teknologi Mara Seri Iskandar, Perak / Nor Maziah Ishak and Natasha Khalil - Ishak, Nor Maziah; Khalil, Natasha (2020)
Malaysia is among one of the development countries that growing rapidly in all sectors which include the sector in construction. One of the components that need attention is the defects in buildings. The aim of this study is to prioritize in the solution towards reducing defects in the hostel building in UiTM Seri Iskandar, Perak using matrix analysis. Objectives of this study are to identify the category of defect that occur at the hostel buildings, to identify the causes of defect that occur at the hostel buildings and to access the priority of reducing the defects in the hostel buildings in UiTM Seri Iskandar, Perak using matrix analysis. A quantitative research was conducted to five respondents who experienced in identify defects at student's resident college in UiTM Seri Iskandar, Perak. Findings from this research revealed that lack of maintenance and climatic condition are the causes of defect that occur at the buildings. Both selected hostel building are in median condition and the affected area need to be rectify. In conclusion, defect that occur need to be rectify to ensure the life span of the building longer.